Transgenic banana expressing Pflp gene confers enhanced resistance to Xanthomonas wilt disease - Namukwaya, B.; Tripathi, L.; Tripathi, J.N.; Arinaitwe, G.; Mukasa, S.B.; Tushemereirwe, Wilberforce K. (Springer, 2012)
Banana Xanthomonas wilt (BXW), caused by Xanthomonas campestris pv. musacearum, is one of the most important diseases of banana (Musa sp.) and currently considered as the biggest threat to banana production in Great Lakes region of East and Central Africa. The pathogen is highly contagious and its spread has endangered the livelihood of millions of farmers who rely on banana for food and income. The development of disease resistant banana cultivars remains a high priority since farmers are reluctant to employ labor-intensive disease control measures and there is no host plant resistance among banana cultivars. In this study, we demonstrate that BXW can be efficiently controlled using transgenic technology. Transgenic bananas expressing the plant ferredoxin-like protein (Pflp) gene under the regulation of the constitutive CaMV35S promoter were generated using embryogenic cell suspensions of banana. These transgenic lines were characterized by molecular analysis. After challenge with X.campestris pv. musacearum transgenic lines showed high resistance. About 67% of transgenic lines evaluated were completely resistant to BXW. These transgenic lines did not show any disease symptoms after artificial inoculation of in vitro plants under laboratory conditions as well as potted plants in the screen-house, whereas non-transgenic control plants showed severe symptoms resulting in complete wilting. This study confirms that expression of the Pflp gene in banana results in enhanced resistance to BXW. This transgenic technology can provide a timely solution to the BXW pandemic.